Entrepreneurship: predictive profiling a game changer. Issue 2 (7th January 2014) - Middleton, Simon
Abstract : Purpose: – Addresses the subject of the entrepreneur, describes the significant and growing number of small and medium-sized enterprises in the UK, and outlines the author's development of an entrepreneurial competency profile (ECP). Design/methodology/approach: – Draws on statistics taken form the UK government-sponsored Young Report, Make Business Your Business, and the author's own research into entrepreneurial efficacy. Findings: – Describes how governments in developed countries and those in emerging nations are driving to create an environment that nurtures and sustains entrepreneurship. They believe it can rapidly create jobs, improve GDP and increase long-term productivity. Practical implications: – Will benefit those in senior management positions by discussing the use of predictive profiling techniques to facilitate wealth creation. Originality/value: – With so much attention being paid to entrepreneurship, and given our knowledge of predictive behavioral economics, can it be justifiably classified as a relatively distinct field in organizational sciences? Whilst there are many notable entrepreneurial successes, there are equally a large number of failures. How can we mitigate the failure rate?